Analisis Kesalahan Siswa dalam Menyelesaikan Soal Program Linier di SMA Negeri 10 Pontianak - Dinda Filzah Nasyanovariani (Journal on Education, 2024)
This research aims to describe students' mistakes in solving linear programming problems for class XI IPA 3 students at SMA Negeri 10 Pontianak. The data instrument is in the form of a test. The test is carried out as a result of student work in the form of a linear program essay. Interviews to observe students' level of difficulty in linear programming questions. Linear programming students in the field of mathematics study class The percentage of errors in KD 4 questions making the HP area and completion point was 25.46% with an average of linear programming material in KD 1, KD 2, KD 3, and KD 4 of 23.40% in the Low category. This type of error falls into the most dominant category, namely errors in understanding the questions